2008
DOI: 10.1097/paf.0b013e3181832432
|View full text |Cite
|
Sign up to set email alerts
|

Death Related to Nasal Surgery

Abstract: The investigation of deaths that are suspected to be related to medical therapy present several challenges for the forensic pathologist. In all such cases, it is important for the pathologist to understand the therapy/procedure that may have played a role in death. As such, review of medical records and possible consultation with various medical specialists before autopsy can provide valuable information to ensure proper evaluation in any given case.Herein, we describe a rare death occurring as a complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Death related to nasal surgery is also rare. In India, Alexander et al (2008) reported that a healthy 58-year-old woman who underwent nasal polypectomy, septoplasty, and intranasal endoscopic ethmoidectomy died 2 days after surgery due to the following brain injuries: subarachnoid hemorrhage, intraventricular hemorrhage, and hydrocephalous, all related to damage of the cribriform plate (5) fered a ventricular hemorrhage and hydrocephalous due to a skull base injury after septoplasty, and died 1 month later (6). Here, we describe a very rare intracranial complication after septorhinoplasty, as awareness of these rare complications can help physicians in prevention, early detection, and appropriate treatment of life-threatening complications.…”
Section: Introductionmentioning
confidence: 99%
“…Death related to nasal surgery is also rare. In India, Alexander et al (2008) reported that a healthy 58-year-old woman who underwent nasal polypectomy, septoplasty, and intranasal endoscopic ethmoidectomy died 2 days after surgery due to the following brain injuries: subarachnoid hemorrhage, intraventricular hemorrhage, and hydrocephalous, all related to damage of the cribriform plate (5) fered a ventricular hemorrhage and hydrocephalous due to a skull base injury after septoplasty, and died 1 month later (6). Here, we describe a very rare intracranial complication after septorhinoplasty, as awareness of these rare complications can help physicians in prevention, early detection, and appropriate treatment of life-threatening complications.…”
Section: Introductionmentioning
confidence: 99%